Relationship and Prevalence of Death Anxiety and Religious Coping among Death Care Workers in Pakistan - Lubaba Tufail, Wajeeha Riaz, Vania Rizvi, Sana Imtiaz, Zarbab Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Death is an inevitable experience that may generate a reduced sense of safety and strong apprehension in humans. Some jobs that require the workers to deal with human deaths, corpses, and people grieving the loss of their loved ones for a larger part of their professional existence such as graveyard workers, morgue workers, ambulance drivers, and emergency medical workers, possess the potential to impact their death anxiety.Given this, the study aims to find the prevalence of death anxiety among death care workers, as hypothesized that the nature of professions would impact the levels of death anxiety, and the positive religious coping would be negatively correlated with the death anxiety while the negative religious coping to be positively correlated to the death anxiety. Design: The sample consists of Pakistani, adult males and females (N=200), belonging to the aforementioned professions. Moreover, the study follows quantitative survey-based research design, using Templer’s Death Anxiety Scale (DAS)-Urdu version and Pargament’s Brief R-COPE-Urdu version Scale. For this purpose, a variety of hospitals, cemeteries, and mortuaries around Karachi were visited to gather relevant data. Findings: The results indicate that the levels of death anxiety varied across all professions, wherein the highest death anxiety was experienced by graveyard workers in contrast to ambulance drivers who had the lowest. With reference to religious coping, positive coping surpassed negative coping and emerged as the superior coping. However, there was no significant correlation between death anxiety and religious coping (positive and negative). Conclusion: This study exhibited some significant patterns of interest but encompasses the potential for further replication. Keywords: Death anxiety, prevalence, religious coping, death care workers, emergency medical workers